KENAKALAN PELAJAR DALAM KELUARGA SINGLE PARENT: STUDI KASUS PADA PELAJAR DALAM KELUARGA SINGLE PARENT DI SEKOLAH MENENGAH ATAS NEGERI 1 GIRIMARTO, WONOGIRI TAHUN 2012/2013 - sri wahyuni; RB Soemanto; Bagus Haryono (Jurnal Analisa Sosiologi, 2015)
Student deliquency is a deviant behavior by students that plaguing thesociety. The purposes of this research were to determine how the forms ofstudent deliquency, the caused factors and the efforts to address studentdelinquency in single parent family in first state SMA of Girimarto. Theresearch method was used descriptive case study. The theory used is theHerbert Blummer’s symbolic interactionism theory. The results showed thatthe forms of student delinquency in a single parent family in first state SMA ofGirimarto are sociological delinquency and individual delinquency. Thecaused factor is children inside and outside factor that is single parent families.Efforts made by first state SMA of Girimarto in handling students delinquencyin single parent families are includes of spiritual building, support grouptherapy, application of school rules were tightened, teens posyandu, lesson inKinanthi song and to their parents for guidance and supervision.Keywords: Delinquency, families, single parent, students.